Occurrence of the complete cycle of Puccinia sorghi Schw. in Argentina and implications on the common corn rust epidemiology - Guerra, Fernando Andres (2018)
The life-cycle of Puccinia sorghi, a heteroecious fungus, consists of five well-defined spore stages. The uredinial and telial stages are completed on the primary host (maize) whereas spermagonial and aecial stages occur on Oxalis spp., a perennial and widespread weed. Portions of corn leaves with telia were surface sterilized and placed in Petri dishes with 2% water agar and maintained in a growth chamber at 25 ± 1 °C and photoperiod of 16 h light and 8 h dark for 48 h to induce the formation of basidia and basidiospores. Oxalis conorrhiza plants were inoculated with those basidiospores, to confirm the generation of spermagonia with spermatia, and subsequently aecia with aeciospores. Corn plants were then inoculated with aeciospores to confirm the formation of urediospores and teliospores. The aecial phase of common corn rust was confirmed to occur on O. conhorriza and the descriptions of spore stages in Argentina are now reported in this work, confirming a potential sexual source of variability of P. sorghi. The natural occurrence of aecial infections on O. conhorriza in Córdoba may play an important role in generating new variants of P. sorghi in Argentina, allowing a constant adaptation of the pathogen to the environment of the different corn production zones.